Punctuation and Implicit Prosody in Silent Reading: An ERP Study Investigating English Garden-Path Sentences - Drury, John E.; Baum, Shari R.; Valeriote, Hope; Steinhauer, Karsten (Frontiers in Psychology, 2016)
This study presents the first two ERP reading studies of comma-induced effects of covert (implicit) prosody on syntactic parsing decisions in English. The first experiment used a balanced 2 x 2 design in which the presence/absence of commas determined plausibility (e.g., John, said Mary, was the nicest boy at the party versus John said Mary was the nicest boy at the party). The second reading experiment replicated a previous auditory study investigating the role of overt prosodic boundaries in closure ambiguities (Pauker et al., 2011). In both experiments, commas reliably elicited CPS components and generally played a dominant role in determining parsing decisions in the face of input ambiguity. The combined set of findings provides further evidence supporting the claim that mechanisms subserving speech processing play an active role during silent reading.